2021
DOI: 10.1176/appi.ajp.2020.20121686
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Clinical, and Sociodemographic Factors Associated With Stimulant Treatment Outcomes in ADHD

Abstract: Objective: Stimulant-drugs are effective for treating attention-deficit/hyperactivity disorder (ADHD), yet discontinuation and switch to non-stimulant ADHD-drugs is common. This study aimed to identify genetic, clinical and socio-demographic factors influencing stimulant-treatment initiation, discontinuation and switch to non-stimulants in individuals ADHD. Methods:We obtained genetic and national-register data for 9,133 individuals with ADHD from the Danish iPSYCH2012 sample, and defined stimulant-treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…In more recent years, ADHD is still frequently underdiagnosed or misdiagnosed as other psychiatric conditions such as mood or personality disorders ( 10 ). Even when patients are diagnosed with ADHD as children, many patients lose access to resources when transitioning from child to adult health services ( 11 ) which may contribute to less than half of people with ADHD adhering to stimulant medication ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years, ADHD is still frequently underdiagnosed or misdiagnosed as other psychiatric conditions such as mood or personality disorders ( 10 ). Even when patients are diagnosed with ADHD as children, many patients lose access to resources when transitioning from child to adult health services ( 11 ) which may contribute to less than half of people with ADHD adhering to stimulant medication ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…PRS for ADHD was found to predict a favorable response to ADHD medication (MPH or ATX), explaining around 2% of the variance [63]. The aforementioned Danish study did not find the PRS for ADHD to be associated with treatment outcomes [64], consistent with recent evidence that genes implicated in the pathogenesis of ADHD do not overlap with genes encoding targets of stimulants and ATX [67]. However, PRS for bipolar disorder and schizophrenia increased the likelihood of stopping stimulant medication (~5-7% of the variance) [64], mirroring findings that comorbid bipolar or psychotic disorders are associated with poor treatment response and adverse events.…”
Section: Geneticsmentioning
confidence: 85%
“…As large sample sizes are needed in GWAS of complex phenotypes such as medication response, studies including less than 250 participants found no genome-wide significant SNPs tied to medication response [62,63]. More promising results come from a large Danish study that linked genotype data with medical records, allowing a well-powered GWAS of starting (N = 7427) or stopping (N = 3370) MPH treatment or switching to non-stimulants (N = 1137) over 2 years [64]. While no genome-wide significant associations emerged for starting or stopping treatment, a locus on 16q23.3 containing genes associated with many neuropsychiatric phenotypes was associated with switching medications, likely due to poor efficacy.…”
Section: Geneticsmentioning
confidence: 99%
“…Symptoms that are often associated with ADHD such as emotional or affect lability for which the efficacy of current agents is inadequate can serve as the examples for this approach. Summary of findings using genome-wide method ( Mick et al, 2008 ; Pagerols et al, 2018 ; Hegvik et al, 2019 ; Zhong et al, 2020 ; Brikell et al, 2021 ) is also provided in Table 2 .…”
Section: Introductionmentioning
confidence: 99%